ANALISIS PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN NASABAH UNTUK MENABUNG DENGAN BRAND EQUITY SEBAGAI VARIABEL MEDIASI - Fenanda, Zakiah Intan; Solekah, Nihayatu Aslamatis (Fakultas Ekonomi, UIN Maliki Malang, 2018)
The development and dynamics of marketing of banking services products help to grow the variables that facilitate the influence of word of mouth against the decision to save. One of it is the brand equity that is a set of assets that is associated with a brand that adds or reduces the value of the company in the views of customers. The purposes of the research are to determine the influence of word of mouth against the decision to save through Brand Equity on the customer of Syariah BRI Bank of Malang.Â The research used a quantitative approach with survey method. The population of the research was all customers of Savings at Syariah BRI Bank of Malang. Sampling technique used accidental sampling with the number of respondents as much as 100 respondents. Â The dependent variable in the research was Savings Decision (Y), and the independent variable was Word of Mouth (X), with Brand Equity (M) as the mediation variable. Data analysis technique used Path Analysis.Â The research results indicated that the dimensions of word of mouth are Talkers, Topics, Taking Part and Tracking that directly influence against brand equity, and one dimension of word of mouth of tools have no effect against brand equity. Brand Equity directly influences the decision to save, all dimensions of word of mouth directly influence the decision to save, and Brand Equity can mediate the indirect influence of word of mouth against the savings decision